A Systematic Review of Outcomes Following Breast Implant-Associated Anaplastic Large Cell Lymphoma (BIA-ALCL). (December 2022) - Sharma, Kavita; Gilmour, Adam; Jones, Georgina; O'Donoghue, Joseph M.; Clemens, Mark W.
Summary and Keywords: Background: Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) has increasingly become a significant concern for patients. Focus thus far has been on understanding pathogenesis and establishing treatment pathways. There has been less attention on the assessment of long-term treatment outcomes. The purpose of this study was to perform a systematic review to assess published data on treatment outcomes for BIA-ALCL. Methods: Using PRISMA guidelines, a systematic search of the literature was carried out from January 1997 to January 2021 using the Web of Science (PubMed) and Ovid Medline. Included in the review were any studies on the management and follow-up of patients, including disease status at a minimum of 18 months following treatment. Results: A total of 39 articles matched the inclusion criteria. However, 94% of patients were managed with explantation and capsulectomy. Then, 39% of patients had adjuvant chemotherapy, 19% radiotherapy, 6% autologous stem cell transplant, and 4% immunotherapy. The mean follow-up was 19 months (range 3–36 months), and 69% of patients were reported to be alive at 18 months. The mainstay of treatment was surgical – en bloc capsulectomy with adjuvant treatment for advanced disease. Conclusions: Robust survival data based on high-level evidence are challenging to establish in BIA-ALCL. Early diagnosis and en bloc capsulectomy with negative margins, whilst considering the need for adjuvant treatment, particularly targeted immune therapy in advanced disease represents the consistent forms of treatment. National databases, prospective studies, and treatment of patients in tertiary centres are all recommended to improve the quality of the research available in the management of BIA-ALCL.